An argument for the academic scrutiny of African Instituted Church (AIC) texts - Manyawu, Andrew T. (Midlands State University, 2015)
This article argues for the rigorous academic scrutiny of Zimbabwean African Instituted Church (AIC) texts, such as African Apostolic Church (AAC) founder Paul Mwazha’s The Divine Commission of Paul Mwazha of Africa. Using Mwazha’s case as an example, the article discusses relevant aspects of Zimbabwe’s socio-cultural history as constituting the context in which the AIC founder has developed a particular discursive practice, including a founding text, to insert himself as a ‘world-historical figure’ into the national history and that history into his own identity and that of the church he formed. The article concludes that the novelty of AICs resides in the fact that texts such as Mwazha’s show that colonised Africans challenged the hegemonic order established by their European masters by insisting on their basic rights, such as human dignity and self-determination, leading to the formation of their own churches. Academic scrutiny of AIC texts will therefore reveal strategies used to attain this hegemonic goal and how this has shaped past and contemporary African identities.